1968
DOI: 10.1152/ajplegacy.1968.214.3.561
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood flow distribution produced by central sciatic nerve stimulation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…In contrast to vestibular afferents, stimulation of limb nerves elicited an increase in resistance and a decrease in conductance in all three vascular beds that were studied, accompanied by tachycardia and blood pressure increases. These observations are consistent with findings from other studies (2,8,17), indicating that pressor responses accompanied by widespread sympathetically mediated vasoconstriction occur in response to electrical stimulation of somatic nerves in anesthetized cats and dogs. In an earlier study, we reported that the pattern of responses of visceral sympathetic nerves to vestibular stimulation is different from that elicited by activation of limb afferents (10).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to vestibular afferents, stimulation of limb nerves elicited an increase in resistance and a decrease in conductance in all three vascular beds that were studied, accompanied by tachycardia and blood pressure increases. These observations are consistent with findings from other studies (2,8,17), indicating that pressor responses accompanied by widespread sympathetically mediated vasoconstriction occur in response to electrical stimulation of somatic nerves in anesthetized cats and dogs. In an earlier study, we reported that the pattern of responses of visceral sympathetic nerves to vestibular stimulation is different from that elicited by activation of limb afferents (10).…”
Section: Discussionsupporting
confidence: 93%
“…iNOS expression in normal skeletal muscles of various species has been investigated recently. iNOS protein expression was not detected in different skeletal muscles of pathogen-free rats (10,12). The current study confirms the absence of iNOS protein expression in normal rat muscles.…”
Section: Discussionsupporting
confidence: 82%
“…With respect to the femoral region, such variability may also be attributable to differences in degree of partici pation of skin and muscle vascular beds as in the adult cat (14), since the femoral artery in the pig supplies both cutaneous and muscular beds (24). During high frequency or intensity stimulation of the sciatic nerve, we observed a general increase in Fern F and carotid F but not in Ren F (table III), and a redistribution of cardiac output that has also been observed in adult dogs under pentobarbital anesthesia (8). Our failure to find age-dependence for all vas cular response patterns may be due to unequal maturation of various central and peripheral elements which are required to produce the complex responses (e.g., no information was obtained about venomotor activity in this in vestigation).…”
Section: Pattern O F Total Cardiovascular Response To Afferent Stimulsupporting
confidence: 59%
“…Stimulation of the central cut end of major somatic nerve trunks such as the sciatic nerve can produce either increased or decreased AoP in adult mammals (6,8,14) and in newborn pigs (10,19) depending upon the fiber type excited by a given set of stimulation parameters (3,20). We found clear-cut evidence for an agedependent difference in magnitude of the maxi mum pressor effect to high frequency or high intensity stimulation of the sciatic nerve (ta ble III).…”
Section: Magnitude O F Arterial Pressure Effects O F Afferent Stimulamentioning
confidence: 67%